2003
DOI: 10.1074/jbc.m306318200
|View full text |Cite
|
Sign up to set email alerts
|

A PTEN-related 5-Phosphatidylinositol Phosphatase Localized in the Golgi

Abstract: Phosphoinositides play important roles as signaling molecules in different cell compartments by regulating the localization and activity of proteins through their interaction with specific domains. The activity of these lipids depends on which sites on the inositol ring are phosphorylated. Signaling pathways dependent on phosphoinositides phosphorylated at the D3 position of this ring (3-phosphoinositides) are negatively regulated by 3-phosphoinositide-specific phosphatases that include PTEN and myotubularin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 56 publications
1
26
0
1
Order By: Relevance
“…A TLC analysis of the reaction products, shown in Fig. 2A, revealed that PLIP exhibits a highly selective substrate specificity for PI(5)P. This substrate preference is shared by the Dictyostelium ortholog of PLIP (30). As expected, the mutation of the predicted catalytic cysteine residue to serine (C132S) nullified this activity.…”
Section: Identification Of Plip As a Pten-likementioning
confidence: 94%
“…A TLC analysis of the reaction products, shown in Fig. 2A, revealed that PLIP exhibits a highly selective substrate specificity for PI(5)P. This substrate preference is shared by the Dictyostelium ortholog of PLIP (30). As expected, the mutation of the predicted catalytic cysteine residue to serine (C132S) nullified this activity.…”
Section: Identification Of Plip As a Pten-likementioning
confidence: 94%
“…A phosphatase with a highly specific 5-phosphatase activity towards PtdIns5P in vitro has been described in mammals (Merlot et al 2003;Pagliarini et al 2004). This enzyme, originally named phospholipid-inositol phosphatase and later renamed PTPMT1 (Blero et al 2007), can potentially convert PtdIns5P to PtdIns but whether this enzyme has a role in reducing the levels of PtdIns5P in vivo is not clear.…”
Section: Phosphatasesmentioning
confidence: 97%
“…This phosphatase harbours a transmembrane domain in its N terminus. It has only a weak overall similarity to PTEN and, in contrast to the 3-phosphatase activity of PTEN, has a highly specific 5-phosphatase activity against PtdIns5P in vitro [79]. PLIP is unrelated to the inositol polyphosphate 5-phosphatase family ( Fig.…”
Section: Phospholipid-inositol Phosphatase (Plip)mentioning
confidence: 99%
“…A search in a Dictyostelium sequence data base for additional PTEN homologs revealed the existence of a new family of phosphatases with orthologs in eukaryotes Bipolar disorder [122] Lethal (−/−) [23] and prokaryotes [79,97]. In mammals, a similar PTEN-like phosphatase, initially called phospholipid-inositol phosphatase (PLIP), has been described.…”
Section: Phospholipid-inositol Phosphatase (Plip)mentioning
confidence: 99%